Creativity and Innovation in Making Handicraft Products for Developing Students Entrepreneurship Spirit - Mei Ie; Hetty Karunia Tunjungsari (MITRA: Jurnal Pemberdayaan Masyarakat, 2020)
Student creativity is the ability that the students have to discover and create new things, new ways, new models that are useful for students in the learning process. Developing handicraft skills is a means of creativity that students must develop. The purpose of this community-service activity was to develop the entrepreneurship spirit of students through the business idea of making handicraft products which would be exhibited in the market day activities at Al Jannah Islamic Nature and Science School Middle School. Lectures and workshops on creativity and innovation in handicraft making were used to develop the entrepreneurship spirit of students. The result of this activity showed that students were able to implement creativity and innovation, especially in making handicraft products that were exhibited in market day activities organized by the school. It was concluded that this activity enabled the students to obtain a business idea in making handicraft products that were exhibited in the market day activities at